Teacher Private Teacher Learning Management Application in SMP IT Nurul Ilmi - Neli Wati; Nanda Putri Khafifah; Rina Yanti; Alpiq Riski; Gunawan Ritonga (Universitas Muhammadiyah Enrekang, 2022)
Learning management is a very important thing that must be done by every teacher in every educational institution with the aim that a learning process can be structured so that the implementation process can run according to a predetermined plan. The research method used in this study is a qualitative research method where researchers get information from the interview process and documentation as well as observations at SMP IT Nurul Ilmi. The results of a research process carried out at SMP IT Nurul Ilmi got the results that teachers, especially craft teachers at SMP IT Nurul Ilmi carried out the learning process in accordance with predetermined procedures by carrying out a planning and organizing process so that with the existence of a planning and organizing process that carried out by teachers at SMP IT Nurul Ilmi can achieve a predetermined process. The conclusion is that SMP IT Nurul Ilmi has carried out its duties in learning management properly and correctly.